Pengunaan Pembelajaran ATI (Aptitude Treatment-Interaction) Dalam Upaya Peningkatan Pemahaman Perkembangbiakan Tumbuhan Pelajaran Ipa pada Siswa Kelas VI SDN Sampurna 2 - Nyai Erot Mali (JURNAL PENDIDIKAN, 2020)
This research is based on the following problems: a) Does the Skills Approach learning affect the learning outcomes of Natural Sciences ?; b) How high is the level of mastery of Natural Science subject matter with the application of the Quantum Teaching learning method? The objectives of this study are: a) To reveal the effect of learning the Skills Approach on learning outcomes in Natural Sciences; b) Want to know how much understanding and mastery of Natural Science subjects after the application of Quantum Teaching learning. This study used three rounds of action research. Each cycle consisted of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is Grade VI students. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (60%), cycle II (80%), cycle III (95%). The conclusion of this study is the Skills Approach method can have a positive effect. SDN Sampurna 2 students' motivation to learn and this learning model can be used as an alternative to Natural Science.